Peranan Bakat dalam Optimasi Pembelajaran Matematika di Perguruan Tinggi - Fitriani, Fitriani; Neviyarni, Neviyarni; Afdal, Afdal (Indo-MathEdu Intellectuals Journal, 2025)
Talent is an innate potential that plays a significant role in the success of mathematics learning in higher education, but its development still faces various obstacles. This study aims to review the latest literature (2020–2025) on the role of talent in mathematics learning, focusing on the definition of talent, types of talent, internal and external factors that influence it, and its relationship with learning interest. This literature review shows that mathematical talent is not limited to cognitive aspects, but also includes creative, visual-spatial, social, and psychomotor abilities. Internal factors such as cognitive abilities, motivation, and interest, as well as external factors such as family support, school, and educational policies, have been shown to greatly influence the development of student talent. The results of the study also confirm that talent without interest tends to be difficult to develop, while interest can strengthen motivation and perseverance in honing talent. In this context, educators play a central role as facilitators and motivators through strategies such as early talent identification, differentiated learning, extracurricular activities, collaboration with parents, and continuous evaluation. Thus, student talent development requires a holistic approach that integrates innate potential, motivation, and environmental support for optimal learning outcomes